PERAN POLISI RUKUN WARGA (RW) SEBAGAI PILAR KEAMANAN DAN KETERTIBAN DI RW08 KELURAHAN PANGKALAN KERINCI TIMUR - Ramadhan, Fahrol; Fakhri Usmita, (Sisi Lain Realita, 2023)
Building a sense of security and order in the residential environment is a crucial factor for creating a peaceful community life. This qualitative research examines the strategic role of the Rukun Warga Police (Polisi RW) as the front guard in realizing security and order in Pangkalan Kerinci Timur Subdistrict, especially in the RW 08 Using the perspective of Social Reaction Theory, it reveals how the RW Police carry out their function as pillars. environmental security through mobile patrols, early detection of security disturbances, mediation of conflicts between residents, as well as close coordination with Bhabinkamtibmas, RW/RT administrators, and active community participation. Data was obtained through interviews with sources including the RW Police, Bhabinkamtibmas, RW heads, RT heads, and the community. The majority of residents responded positively to the presence of the RW Police, which increased their sense of security, there were no challenges, everyone liked the program and the presence of the police was harmonious with the residents. To optimize performance, continuous efforts are needed, such as increasing personnel capacity through training, providing adequate facilities, and developing crime prevention programs that involve massive citizen participation. It is hoped that in the future, the RW Police can continue to mobilize community participation, increase the capacity of members, improve coordination with various parties, and optimize programs that involve residents. Overall, RW Police have an important role by coordinating and involving active community participation.